Strategi Sekolah Dalam Membangun Kemitraan Kolaboratif Dengan Stakeholder - Erfiana, Lisa; Fradito, Aditia; Yetri, Yetri (Jurnal Kependidikan, 2025)
This study aims to explore the strategic role of the school in building a collaborative partnership with parents of students with special needs at Sekolah Dasar Luar Biasa Negeri Sukamaju, Lampung Utara, Indonesia. It contributes to the existing body of knowledge by addressing the research gap op comprehensive school strategies in special education contexts in Indonesia. A qualitative approach with a phenomenological perspective was used to examine the formulation, implementation, and evaluations of collaboration strategies. Data were collected through in-depth interviews, observation, and document analysis. The results show that the strategy was carried out through parenting programs, two-way communication via WhatsApp, and life skills training for students. This approach successfully enhanced parental involvement, fostered strudent independence, and helped create a supportive school environment.